Riders of justice [videorecording (DVD)] = Retfærdighedens ryttere - Jensen, Anders Thomas, 1972-; Mikkelsen, Mads, 1965-; Kaas, Nikolaj Lie, 1973-; Gadeberg, Andrea Heick (Magnolia Home Entertainment, 2021)
Markus, who has to go home to his teenage daughter, Mathilde, when his wife dies in a tragic train accident. It seems like an accident until a mathematics geek, who was also a fellow passenger on the train, and his two colleagues show up.